PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT SEBAGAI UPAYA DALAM MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA DALAM PEMBELAJARAN INTEGRAL TAK TENTU - Made Dharma Atmaja (Jurnal Santiaji Pendidikan (JSP), 2015)
Based on observations in class XI of Saraswati 2 Denpasar Vocational High School, several obstacles were found when learning took place, including (1) student involvement in learning was still lacking, (2) students were less prepared to take part in learning, (3) lack of collaboration between students in completing assignment, (4) students have not been able to conclude the material being studied. In accordance with the file taken through interviews with the mathematics teacher of class XI of Saraswati 2 Denpasar Vocational High School, information the achievement of mathematics learning is categorized as low, because it has not reached the minimum completeness criteria that have been established of Saraswati 2 Denpasar Vocational High School. This study uses a qualitative approach and this type of research is a classroom action study (CAR). This research was carried out for up to two cycles. The percentage increase in the average score of student learning activities from cycle I to cycle II is 43.31% and the percentage increase in the average value of student learning achievement, learning completeness, and absorption from cycle I to cycle II are respectively: 8, 31%; 31.99%; and 8.31%. Based on the results of this study, it can be concluded that the activities and student achievement in integral learning are not necessarily algebraic functions through the application of NHT type cooperative learning model in class XI students of Saraswati 2 Denpasar Vocational High School 2014/2015 of the academic year has increased.